2020
DOI: 10.1177/1078155219900944
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tumor regression grade on long-term survival in locally advanced rectal cancer treated with preoperative chemoradiotherapy

Abstract: Purpose The aim of this study is to investigate the prognostic effect of tumor regression grade (TRG) on long-term survival in locally advanced rectal cancer treated with preoperative chemoradiotherapy. Methods Medical records of 182 patients with locally advanced rectal cancer, who were treated with preoperative chemoradiotherapy followed by surgery between 2002 and 2016, were retrospectively reviewed. TRG was classified into five categories based on the pathological response as follows – TRG1: no viable canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
6
2
Order By: Relevance
“…Recent cPR rates after neoadjuvant CRT are reported to be between 10.4 and 33.9% [34][35][36][37][38][39][40]. The heterogeneity of the rates may be partially explained by the use of different TRG systems and the additional subgrouping of the patients with complete and near-complete/intermediate responses in one group [35,39,41].…”
Section: Discussionmentioning
confidence: 99%
“…Recent cPR rates after neoadjuvant CRT are reported to be between 10.4 and 33.9% [34][35][36][37][38][39][40]. The heterogeneity of the rates may be partially explained by the use of different TRG systems and the additional subgrouping of the patients with complete and near-complete/intermediate responses in one group [35,39,41].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, pCR has been shown to increase survival rates. Having known the parameters that will predict pCR before treatment will strengthen the clinician's treatment-decision making [10,34].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that pathological complete response (pCR) increases survival rates [4][5][6][7][8]; however, only 15-25% of rectal cancer patients can achieve pCR [9,10]. Therefore, the question of surgical necessity has been raised for this group of patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…however, only 15-25% of rectal cancer patients can achieve pCR [9,10]. Therefore, the question of surgical necessity has been raised for this group of patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, pCR has been shown to increase survival rates. Having known the parameters that will predict pCR before treatment will strengthen the clinician's treatment-decision making [10,34].…”
mentioning
confidence: 99%